2013
DOI: 10.1117/1.jbo.18.4.045003
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring hemodynamic and morphologic responses to closed head injury in a mouse model using orthogonal diffuse near-infrared light reflectance spectroscopy

Abstract: The authors' aim is to assess and quantitatively measure brain hemodynamic and morphological variations during closed-head injury (CHI) in mice using orthogonal diffuse near-infrared reflectance spectroscopy (o-DRS). CHI is a type of injury to the head that does not penetrate the skull. Usually, it is caused by mechanical blows to the head and frequently occurs in traffic accidents, falls, and assaults. Measurements of brain optical properties, namely absorption and reduced scattering coefficients in the wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…Assuming that the concentration of red blood cells (hematocrit level) remains constant following injury, THC can be used as a surrogate marker of CBF. Reduced CBF following brain trauma observed here is consistent with our previous studies 34,35 and stands in agreement with results of neuroimaging studies, which revealed heterogeneous regional disturbances of CBF. [50][51][52] Under decreased CBF, brain cells undergo a series of pathophysiologic changes further complicated by decreased oxygen supply, as reflected in lowered StO 2 , contributing to secondary injury.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Assuming that the concentration of red blood cells (hematocrit level) remains constant following injury, THC can be used as a surrogate marker of CBF. Reduced CBF following brain trauma observed here is consistent with our previous studies 34,35 and stands in agreement with results of neuroimaging studies, which revealed heterogeneous regional disturbances of CBF. [50][51][52] Under decreased CBF, brain cells undergo a series of pathophysiologic changes further complicated by decreased oxygen supply, as reflected in lowered StO 2 , contributing to secondary injury.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, it appears that morphine was able to delay or prevent the gradual decrease of sp seen in untreated TBI. 34,35 This delay in cell swelling, probably reflecting a decrease in ICP, is in agreement with Lauer et al, who reported that morphine administration preserves systemic arterial pressure without elevating ICP in head injury patients. 63 It should be stressed that the clinical effectiveness of morphine for the reduction of ICP in severe head injury remains open to question.…”
Section: Figures 4(a) and 4(b)supporting
confidence: 79%
See 3 more Smart Citations